Implementasi Pendekatan Holistic-Diagnostic Approach untuk Mengoptimalkan Kapabilitas Fondasi Dasar dan Penguatan Identitas Kultural-Religius Siswa Sanggar Bimbingan Sungai Buloh - Tsaqibul Fikri, Mohammad; Chandra Sari, Astrid; Ulfa, Ulfa; Norlina Binti Samad, Siti; Khoirun Nisa, Indah; Khasanah, Imroatun; Rainowati, Latasyah (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
This Community Service Program (PKM) aimed to address fundamental educational challenges—namely the low basic skills in Literacy and Numeracy, and the limited understanding of National Insight (Wawasan Kebangsaan) and Religious Knowledge—among students at the Learning Center (Sanggar Belajar or SB) Sungai Buloh, Selangor, Malaysia. The main issues identified included poor basic reading, writing, and arithmetic (calistung) abilities, along with limited access to adequate formal education. The PKM Team implemented an Integrated Intervention Model combining creative learning methods and educational games based on interactive media (such as flashcards, the “10 Menit Lancar Membaca” book, and the “Spin and Speak” game). The program was carried out over four weeks, encompassing observation stages, collaborative schedule arrangement with the center's management, material delivery, and achievement evaluation. Evaluation results showed significant improvements across four main indicators:1) Literacy: The average reading ability of participants increased from 58% to 85% (a 27% increase), based on tests of basic vocabulary mastery and simple text comprehension.2) Numeracy: The accuracy of basic arithmetic (addition and subtraction) increased from an average of 65% to 89% (a 24% increase). 2) National Insight (Wawasan Kebangsaan): Knowledge of state symbols and important figures increased by 35% from the pre-test score. 3) Religious Knowledge: The percentage of students capable of memorizing a minimum of five short surahs/daily prayers increased from 40% to 75%. Overall, the approach based on the Holistic-Diagnostic approach proved effective. The tangible contribution of this PKM is not only limited to improving students' cognitive and affective competence but also successfully strengthening social and cultural ties between the program implementers and the local community at SB Sungai Buloh.